2006
DOI: 10.1002/ddr.20066
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal gold nanoparticles: a novel nanoparticle platform for developing multifunctional tumor‐targeted drug delivery vectors

Abstract: Nanotechnology applied to biological problems represents an emerging field with the potential to offer extremely sensitive diagnostics and targeted cancer therapies. However, to achieve these goals, nanoparticle delivery systems must outwit the many barriers that are intrinsic to the body's defenses, as well as those that develop during the growth and progression of tumors. The science is advancing and, for example, true nanoscale tumor-targeted drug delivery vectors are now able to reduce the likelihood of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
275
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(280 citation statements)
references
References 34 publications
2
275
0
3
Order By: Relevance
“…In particular, gold NPs possess biological activities like antioxidant, anti-inflammatory, anti-angiogenesis and anticancer properties and therefore it has been used for the delivery of drugs, proteins, peptides and oligonucleotides etc. [16].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, gold NPs possess biological activities like antioxidant, anti-inflammatory, anti-angiogenesis and anticancer properties and therefore it has been used for the delivery of drugs, proteins, peptides and oligonucleotides etc. [16].…”
Section: Introductionmentioning
confidence: 99%
“…With the invention of large-scale hyperthermia instruments and the wide use of hyperthermia, thermal targeting has become much easier to implement and more precise to control (Johannsen et al, 2006;Paciotti et al, 2006;Sayed et al, 2006;Visaria et al, 2006;Yang et al, 2007Yang et al, , 2009Liu et al, 2008;Shen et al, 2008;Li et al, 2009d). Thermal targeting has the following obvious advantages: (1) Compared to other techniques such as active targeting, it can be applied on a wide spectrum of cancer types as it relies on local heating to confine the release of drugs.…”
Section: Physical and Chemical Targeting Tcm Preparationmentioning
confidence: 99%
“…In fact, colloidal gold has been safely used to treat rheumatoid arthritis for half a century (Root et al 1954;Merchant 1998). Recent work has indicated that pegylated gold nanoparticles (colloidal gold particles coated with a protective layer of polyethylene glycol [PEG]) exhibit excellent in vivo biodistribution and pharmacokinetic properties after systemic injection (Paciotti et al 2006;James et al 2007;Qian et al 2008).…”
Section: Biological Activity Of Immobilized Peptidementioning
confidence: 99%